The citizen’s charter and public service delivery in Bangladesh - Razzaque, Farhana (Routledge, 2022)
This book chapter was published in the book named Public Policy and Governance in Bangladesh Forty Years of Experience and the definite version is available at : https://www.taylorfrancis.com/books/edit/10.4324/9781315621043/public-policy-governance-bangladesh-nizam-ahmed?refId=d2cb7009-b072-4d4d-8c80-275d3cb92692&context=ubx